Knowledge and attitude of pain management among nursing students in Universiti Sains Malaysia (USM) - Ishak, Dayini (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Recognition and assessment of pain are critical aspects in patient care that nurses need to take seriously to make sure patients are comfortable. Education regarding pain and its management is important for nursing students to enhance the quality of life of patients, hence, a cross-sectional study was carried out to assess the level of knowledge and attitude of pain management among nursing students in USM. Data was collected using a selfadministered questionnaire. A total of 86 nursing students from the School of Health Sciences, USM who fulfilled the inclusion criteria were involved in this study. They were selected through a probability simple random sampling method. Data collected were statistically analyzed using the Statistical Package Social Sciences (SPSS) software version of 25. This study shows that 66.3% of respondents have a poor level of knowledge and attitude in pain management. Gender, age and level of the current study were found to have a significant relationship with the level of knowledge and attitude of pain management (p < 0.05). The result of this present study revealed that there is no significant relationship between individual characteristics of and level of knowledge and attitude in pain management among nursing students in USM (p > 0.05). The study finding demonstrated that nursing students in USM have insufficient knowledge and attitudes regarding pain and its management and could benefit from additional education and training on that issue.